Klasifikasi Terjemahan Ayat Al-Quran Tentang Ilmu Sains Menggunakan Algoritma Decision Tree Berbasis Mobile - Devi Setiawati; Ichsan Taufik; Jumadi Jumadi; Wildan Budiawan Zulfikar (Department of Informatics, UIN Sunan Gunung Djati Bandung, 2016)
The number of verses of the Quran contained in the Qur'an, encouraging people to look for a way to get the exact clause in a short time. The science is an important knowledge, as Muslims we are obliged to study it with the Al-Quran as a guide. So that's how we get the verse about the science of the Quran with a quick, efficient and practical with a mobile application. Decision tree is a predictive model using a tree or hierarchical structure, this method can support mobile applications to be created. Because based decision very complex and global in the Quran, can be transformed into more simple and specific. C4.5 algorithm is a decision tree induction algorithm and is suitable to perform the classification process. The results of the percentage of successful applications created by using a decision tree that is 75.73%. From these results is known that the algorithm C4.5 and decision tree reasonably is well used in the classification process.